Urban Forest Recreation and Its Possible Role throughout the COVID-19 Pandemic - Bamwesigye, Dastan; Fialová, Jitka; Kupec, Petr; Yeboah, Evans; Łukaszkiewicz, Jan; Fortuna-Antoszkiewicz, Beata; Botwina, Jakub (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2023)
Urban forests provide benefits in terms of the environment and society. Many people living in urban areas could profit from the recreational services provided by urban forests to alleviate the physical and psychological stresses caused by closure restrictions during the COVID-19 epidemic. However, limited research has been conducted on the role of forest recreation during the COVID-19 lockdown to support future policy decisions regarding such dramatic circumstances. The study aims to investigate the frequency of visitors in the reference Training Forest Enterprise Masaryk Forest Křtiny in Brno, Czech Republic, and to verify if the lockdown led to its intensified use, under the context of weather conditions. Data were collected using a Pyro Box Compact reader and TRAFx Infrared Trail Counter. Regression analysis was performed to determine whether individual weather factors significantly influenced the intensity of forest visitations before and during COVID-19. The number of visits in 2021 during the strict lockdown and post-lockdown periods was significantly higher during spring and autumn than in 2016 and 2017, respectively. The frequency pattern of forest users visibly changed in 2021, and the total number of visits was much higher, even though 2021 had worse weather than the reference years before the pandemic. The results show the recreational use and importance of the forest, especially during the pandemic. This work is a continuation of our previous research with regard to this area, which indicated the importance of forest recreational services for the well-being and health of city dwellers.
Keywords: COVID-19 pandemic; municipal forests; forest recreational services; weather conditions